Molecular cloning and characterization of type III polyketide synthase from Plumbago zeylanica. Issue 5 (4th May 2021) - Sakamoto, Seiichi; Morita, Yui; Yusakul, Gorawit; Putalun, Waraporn; Tanaka, Hiroyuki; Morimoto, Satoshi
Abstract: Two cDNAs encoding type Ш polyketide synthase (PKS1) and chalcone synthase (CHS, PKS2), were cloned from fresh leaves of Plumbago zeylanica L. ( P. zeylanica ). Their heterologous expression revealed that PKS1 catalyzed the formation of five α-pyrones from three to six acetate units by accepting acetyl-CoA and malonyl-CoA. In contrast, PKS2 catalyzed the formation of naringenin and bisnoryangonin by accepting p -coumaroyl-CoA and malonyl-CoA. Naringenin is thought to be involved in the biosynthesis of various bioactive flavonoids. PKS2 can be used to molecular breeding to enhance the production of these useful secondary metabolites via its overexpression.